Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1029/2005gc001204
|View full text |Cite
|
Sign up to set email alerts
|

In situ Raman analyses of deep‐sea hydrothermal and cold seep systems (Gorda Ridge and Hydrate Ridge)

Abstract: [1] The Deep Ocean Raman In Situ Spectrometer (DORISS) instrument was deployed at the Sea Cliff Hydrothermal Field and Hydrate Ridge in July 2004. The first in situ Raman spectra of hydrothermal minerals, fluids, and bacterial mats were obtained. These spectra were analyzed and compared to laboratory Raman measurements of standards and samples collected from the site. Spectra of vent fluid ($294°C at the orifice) at $2700 m depth were collected with noncontact and immersion sampling optics. Compared to spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 41 publications
(54 reference statements)
4
73
0
Order By: Relevance
“…Pure sulfur has little fluorescence under either green or red excitation. The spectral data obtained in this study correspond well to data reported in the literature for elemental sulfur analyzed in the lab (Edwards et al, 1997) and filamentous sulfur produced by bacterial mats analyzed in the lab (Pasteris et al, 2001) and in situ on the seafloor (White et al, 2006b). …”
Section: Elemental Sulfursupporting
confidence: 86%
See 4 more Smart Citations
“…Pure sulfur has little fluorescence under either green or red excitation. The spectral data obtained in this study correspond well to data reported in the literature for elemental sulfur analyzed in the lab (Edwards et al, 1997) and filamentous sulfur produced by bacterial mats analyzed in the lab (Pasteris et al, 2001) and in situ on the seafloor (White et al, 2006b). …”
Section: Elemental Sulfursupporting
confidence: 86%
“…It should be noted that all spectra in this study were obtained in air (unless otherwise noted). Previously collected in situ spectra did not show any effects from seawater, temperature or pressure on the Raman spectra of hydrothermal minerals (White et al, 2005;White et al, 2006b). …”
Section: Laser Raman Spectrometermentioning
confidence: 84%
See 3 more Smart Citations